Harnessing the Collective Expertise of Patients, Care Partners, Clinical Teams, and Researchers Through a Coproduction Learning Health System: A Case Study of the Dartmouth Health Promise Partnership. Issue 2 (April 2023) - Tosteson, Anna N. A.; Kirkland, Kathryn B.; Holthoff, Megan M.; Van Citters, Aricca D.; Brooks, Gabriel A.; Cullinan, Amelia M.; Dowling-Schmitt, Miriam C.; Holmes, Anne B.; Meehan, Kenneth R.; Oliver, Brant J.; Wasp, Garrett T.; Wilson, Matthew M.; et al.
Abstract : The coproduction learning health system (CLHS) model extends the definition of a learning health system to explicitly bring together patients and care partners, health care teams, administrators, and scientists to share the work of optimizing health outcomes, improving care value, and generating new knowledge. The CLHS model highlights a partnership for coproduction that is supported by data that can be used to support individual patient care, quality improvement, and research. We provide a case study that describes the application of this model to transform care within an oncology program at an academic medical center.